Algebraic Methods in Partial Differential Operators (Journal of Partial Differential Equations, 2005)
In this paper we build a class of partial differential operators L having the following property : if u is a meromorphic function in \mathbb{C}^n and Lu is a rational function \frac{A}{q}, with q homogenous, then u is also a rational function.
Keywords: Chow's lemma; regular partial differential operators; meromrphic functions; homogeneous polynomials; Euler's differential operator